2020
DOI: 10.1002/tafs.10273
|View full text |Cite
|
Sign up to set email alerts
|

Robust Recolonization of Pacific Lamprey Following Dam Removals

Abstract: Removal of two dams in the Elwha River basin, Washington, started one of the largest river restoration projects ever attempted in the Pacific Northwest. These dams had eliminated Pacific Lamprey Entosphenus tridentatus populations upstream. After the dam removals, larval production increased in the upper watershed, but the sources and numbers of new adult spawners were unknown. We applied genetic stock identification (GSI), parentage assignment (PA), and sibship assignment (SA) methods to (1) determine the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…The three software programs were chosen because they were well suited for each component of the analysis. Both SNPPIT (Hess et al 2015) and SingleSEQUOIA (Hess et al 2021) have been tested via simulation for accuracy of parent pair and single‐parent assignments in Pacific Lamprey, and both programs run in less than 1 h for data sets of this size. COLONY takes significantly more time than the other parentage programs to analyze similar‐sized data sets (i.e., days) but has been shown to provide accurate pedigrees of full sibship in Pacific Lamprey (Whitlock et al 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three software programs were chosen because they were well suited for each component of the analysis. Both SNPPIT (Hess et al 2015) and SingleSEQUOIA (Hess et al 2021) have been tested via simulation for accuracy of parent pair and single‐parent assignments in Pacific Lamprey, and both programs run in less than 1 h for data sets of this size. COLONY takes significantly more time than the other parentage programs to analyze similar‐sized data sets (i.e., days) but has been shown to provide accurate pedigrees of full sibship in Pacific Lamprey (Whitlock et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative to F ST metrics that use allele frequencies across collections, Mateus et al (2021) proposed the use of individual-level genotypic data to perform either parentage analysis or full-sibship analysis for estimation of migration rates between potential sources and sinks of lamprey production. Hess et al (2021) attempted to apply these parentage and sibship methods to Pacific Lamprey in coastal subbasins but were limited by insufficient recapture data. However, for the Snake River collections described here, these analysis methods were an effective tool for estimating dispersal rates in lampreys and required 4 years of juvenile collection (2011-2014) from one source and 4 years of adult collection (2015-2018) from two different sinks.…”
Section: Parentage and Sibship Analyses Can Estimate Movement Of High...mentioning
confidence: 99%
“…Juvenile Coho Salmon and Chinook Salmon were also seen upstream of each dam, demonstrating that spawning adults and their progeny are utilizing upstream habitats. The reconnection of the Elwha River will have far-reaching implications for genetic diversity, life history diversity, and habitat use of these species, which has started to be documented for Steelhead (Fraik et al, 2021), Pacific Lamprey (Hess et al, 2021), Coho Salmon (Liermann et al, 2017), andBull Trout (Quinn et al, 2017;Lincoln et al, 2018;Brenkman et al, 2019). Although our study was not designed to estimate population sizes, the observed densities increased and there was an upstream shift in the locations of higher density reaches for both trout and Bull Trout.…”
Section: Discussionmentioning
confidence: 87%
“…These studies have demonstrated that molecular methods can be very effective in detecting some prey items compared to traditional morphological methods (Symondson 2002;Carreon-Martinez et al 2011;Sakaguchi et al 2017). Further, genetic analysis is also increasingly being applied to fisheries management through the use of parentage-based tagging to determine the age and origin of sampled fishes (Hess et al 2016(Hess et al , 2021Steele et al 2019). Parentagebased tagging makes use of large numbers of genetic markers to identify the offspring from a data set of candidate parents.…”
mentioning
confidence: 99%
“…Further, genetic analysis is also increasingly being applied to fisheries management through the use of parentage‐based tagging to determine the age and origin of sampled fishes (Hess et al. 2016, 2021; Steele et al. 2019).…”
mentioning
confidence: 99%